Meaning and Truth in the Arts. - Hospers, John (Chapel Hill, North Carolina : University of North Carolina Press, 1974)
Abell, Walter ; Alexander, Samuel ; Arnold, Matthew ; Austen, Jane ; Babbitt, Irving ; Barnes, Albert C. ; Bell, Clive ; Bennett, Arnold ; Bernheimer, Richard ; Bevan, Edwyn ; Binyon, Laurence ; Boas, George ; Botticelli, Sandro ; Bradley, Andrew C. ; Bridges, Robert ; Britton, Karl ; Brooks, Cleanth ; Browning, Robert ; Brueghel, Pieter ; Buermeyer, Laurence ; Bukofzer, Manfred ; Bullough, Edward ; Burke, Kenneth ; Butcher, S.H. ; Carpenter, Rhys ; Carritt, D.F. ; Cézanne, Paul ; Chagall, Marc ; Cheney, Sheldon ; Cohen, Morris ; Collingwood ; Constable ; Corot, Jean-Baptiste Camille ; Courbet, Gustave ; Croce, Benedetto ; Cummings, E.E. ; Debussy, Claude ; Delius, Frederick ; Derain, André ; Dewey, John ; Ducasse, C.J. ; Duret, Theodore ; Eastman, Max ; El Greco ; Eliot, T.S. ; Empson, William ; Foerster, Norman ; Forster, F.M. ; Francis, St. ; Frost, Robert ; Fry, Roger ; Gehring, Albert ; Giles, Herbert A. ; Giotto ; van Gogh, Vincent ; Gorky, Maxim ; Goya ; Grahame, Kenneth ; Greene, Theodore M. ; Grünewald, Matthias ; Gurney, Edmund ; Hanslick, Edouard ; Hardy, Thomas ; Hellman, Lilian ; Heyl, Bernard C. ; Housman, A.E. ; Howells, William D. ; Hulme, T.E. ; James, D.G. ; James, Henry ; James, William ; Jessep, T.E. ; Joad, C.E.M. ; Kandinsky, Wassily ; Klee, Paul ; Knight, G. Wilson ; Knight, Helen ; Láng, Paul H. ; Langer, Susanne K. ; Langfeld, H. ; Lee, Vernon ; Leichtentritt, Hugo ; Lewis, C.L. ; Lewis, Sinclair ; Lucas, F.L. ; Manet ; Mather, F.J. ; Matisse, Henri ; Mauron, Charles ; Michelangelo ; Mill, John Stuart ; Milton ; Mondriaan, Piet ; Monet, Claude ; Moore, Douglas ; Moore, George ; Münsterberg, Hugo ; Murry, J.M. ; Nagel, Ernest ; Newman, Ernest ; Ogden, C.K. ; Parkhurst, Helen H. ; Pater, Walter ; Pepper, Stephen ; Picasso, Pablo ; etc.
Engels
boek